The social class struggles concept with an interdisciplinary approach: a paramount concept for research in library and information science (LIS) - Muela Meza, Zapopan Martín (Universidad Autónoma de Nuevo León, Facultad de Filosofía y Letras, 2010)
This paper analyses the social class struggles concept with an interdisciplinary approach to be used by theorists and practitioners of library and information science (LIS). This concept emerged as part of the theoretical framework employed by the author in his doctoral thesis (Muela-Meza, 2010): An Application of Community Profiling to Analyse Community Information Needs, and Providers: Perceptions from the People of the Broomhall Neighbourhood of Sheffield, UK. This concept is complemented from philosophy (Marx and Engels, [1848] 1976a), and the natural sciences (Hauser, 2006; Sagan and Druyan, 1992), and it served the author to understand better the bigger dimensions of the underlying issues behind social classes and human conflicts. It also served to understand better the contradictions between people (e.g. LIS users with contradictory and mutually exclusive information needs to be provided by libraries and other institutions of information recorded in documents), and how these intensify when these are interrelated with the social class they belong to (Muela-Meza, 2007). This paper also criticises some competing views whose proponents by pretending fallaciously and deceitfully to deny the presence of social class divides in society, such as those rhetorical ploys of post-modernism that propose capitalist-class-driven ideologues of “community cohesion” based on “social capital” (Putnam, 1999). It shows evidence of how those followers (e.g. Pateman, 2006; Contreras Contreras, 2004; Bryson, Usherwood and Proctor, 2003) of capitalist-class ideologues, by doing so they aligned their discourse to that of dominance hierarchies and hegemony against working class people, in LIS and other sciences, and the humanities. It also criticises the postmodern pseudoscience because it pretends to undermine the logical rationality fundamental in LIS and all other sciences. It recommends that LIS theorists and practitioners employ the social class struggles concept as configured here in order to understand better contradictions, conflicts, and struggles within LIS theory and practice, and also to search for broader epistemological aims such as justice and wisdom (Fleissner and Hofkirchner, 1998), concealed by the capitalist or bourgeois and middle classes for their benefit against working class.